2021
DOI: 10.1016/j.jmii.2020.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of health care workers with COVID-19 pneumonia caused by SARS-CoV-2

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 15 publications
5
62
1
7
Order By: Relevance
“…During the early stage of the COVID-19 outbreak, many healthcare workers (HCWs) became infected due to lack of appropriate infection prevention and control protocols and implementation procedures. In Wuhan Union Hospital, 14 HCWs were infected by two index patients in the early days ( 5 ). In Italy, more than 3,300 HCWs had been infected, and at least 22 had died by early March, and by the end of March, COVID-19 had infected 20% of the frontline HCWs, and many had died ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the early stage of the COVID-19 outbreak, many healthcare workers (HCWs) became infected due to lack of appropriate infection prevention and control protocols and implementation procedures. In Wuhan Union Hospital, 14 HCWs were infected by two index patients in the early days ( 5 ). In Italy, more than 3,300 HCWs had been infected, and at least 22 had died by early March, and by the end of March, COVID-19 had infected 20% of the frontline HCWs, and many had died ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…People in close contact, such as family members and travel companions spread SAR‐CoV‐2 readily to each other (Lei et al., 2020; Liu, Fang, et al, 2020; Wang, Pan, et al, 2020). Others in close contact with COVID‐19 patients, such as healthcare providers, are also at increased risk for COVID‐19 (Chu et al., 2020; Huang, Wang, et al, 2020; Li, Peng, et al, 2020; Wei, Wang, Zhang, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Most concerning to practicing nurses is the evidence that there is considerable nosocomial spread of SARS‐CoV‐2 (Mi et al., 2020; Peng et al., 2020). Many COVID‐19 patients are presumed to have been infected in healthcare settings (Chan et al., 2020; McMichael et al., 2020; Mi et al., 2020; Peng et al., 2020; Wang, Liu, et al, 2020; Wei, Wang, Zhang, et al, 2020). Moreover, epidemiological trends indicated that 2.4%–8.2% of all COVID‐19 cases in China were also healthcare workers (Chen, Wu, et al, 2020; Li, Xu, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Transmission dynamics of SARS-CoV-2 are heterogeneously [20]. Numerous individual infection clusters in particular in Asia with variable size have been reported [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Transmission Dynamicsmentioning
confidence: 99%